Immune tolerance induction in patients with haemophilia a and inhibitors: effectiveness and cost analysis in an European Cohort (The ITER Study). (17th August 2015) - Rocino, A.; Cortesi, P. A.; Scalone, L.; Mantovani, L. G.; Crea, R.; Gringeri, A.; ,
Abstract : Introduction: Although immune tolerance induction (ITI) is considered the first choice treatment to eradicate inhibitors in haemophilia A patients, little is known about outcomes determinants and cost magnitude. Aim and Methods: A retrospective, multicentre study was conducted to assess the relationship between ITI outcome, clinical and treatment characteristics and cost of ITI treatment in haemophilia A patients. Data from 12 months before inhibitor diagnosis to 12 months after ITI completion were collected. Treatment cost was calculated in the third‐party perspective and expressed as mean € per patient‐month. Cox regression models were used to identify predictors of better outcome and the time taken to achieve tolerance. Results: Seventy‐one patients, aged 0.4–41 years (median: 3.8 years) at ITI start, were enrolled. Undetectable inhibitor was achieved in 84.5% of patients and inhibitor eradication with normal factor VIII (FVIII) pharmacokinetics in 74.2%. Median time to successful tolerance was 10.7 months (range 2.0–90.0 months). Peak inhibitor level on ITI was a significant predictor of ITI success. Breakthrough bleeding event incidence during ITI was associated with time to success. The mean cost of treatment for the time period between inhibitor diagnosis and ITI start was €3188 per patient‐month (92.1% for bypassing agents), and €60 078 during ITI (76.8% for FVIII use in ITI). Conclusion: Immune tolerance induction in this patient cohort was successful in 84.5% of patients with a mean cost of €60 000 per patient‐month. This high cost is dwarfed by comparison with the prospect of lifelong care of an inhibitor patient, in addition to gains in life expectancy and health‐related quality of life.